Bioprinted Membranes for Corneal Tissue Engineering: A Review - Amin Orash Mahmoud Salehi; Saeed Heidari-Keshel; Seyed Ali Poursamar; Ali Zarrabi; Farshid Sefat; Narsimha Mamidi; Mahmoud Jabbarvand Behrouz; Mohammad Rafienia (Pharmaceutics, 2022)
Corneal transplantation is considered a convenient strategy for various types of corneal disease needs. Even though it has been applied as a suitable solution for most corneal disorders, patients still face several issues due to a lack of healthy donor corneas, and rejection is another unknown risk of corneal transplant tissue. Corneal tissue engineering (CTE) has gained significant consideration as an efficient approach to developing tissue-engineered scaffolds for corneal healing and regeneration. Several approaches are tested to develop a substrate with equal transmittance and mechanical properties to improve the regeneration of cornea tissue. In this regard, bioprinted scaffolds have recently received sufficient attention in simulating corneal structure, owing to their spectacular spatial control which produces a three-cell-loaded-dimensional corneal structure. In this review, the anatomy and function of different layers of corneal tissue are highlighted, and then the potential of the 3D bioprinting technique for promoting corneal regeneration is also discussed.